FEATURES OF PROJECT FINANCING OF REAL ESTATE IN THE DIGITAL ECONOMY AND ITS STATE REGULATION - A. V. Zakharova; V. G. Makeeva; N. V. Kazantseva; O. A. Revzon (Вестник университета)
The problematic issues related to investment processes in the real estate market, based on modern tools of project financing, have been considered. The Russian experience of taxation of investment entities in the Russian Federation, the experience of private-public partnership in the process of investing in real estate objects, have been studied, the problems of using project financing by real estate market entities in the conditions of digitalization have been identified. The directions of improvement of financial, economic, social and legal aspects of state regulation of project financing have been proposed in order to ensure a balance of interests of various economic entities, which as States, firms and households are considered. Modern models of real estate financing by the banking sector have been reviewed.